Recent Advancements Surrounding the Role of the Periaqueductal Gray in Predators and Prey - Franklin, Tamara B. (Frontiers in Behavioral Neuroscience, 2019)
Recent advances in neural circuitry techniques, like optogenetics and chemogenetics, have allowed for a greater understanding of the periaqueductal gray (PAG) and its importance in predator and prey behaviors. These studies in rodents have highlighted the role of the rostrolateral PAG in hunting behaviors, and have demonstrated functional differences across the dorsal-ventral/rostral-caudal axes of the PAG associated with defensive behaviors. Human imaging studies have further demonstrated that the PAG is active during situations involving imminent threat suggesting that the function of the PAG is likely largely conserved across species. This mini-review article highlights some of the recent advancements towards our understanding of the functional neuroanatomy of the PAG and its importance in the predator and prey behaviors that are critical for survival.